Early and School-Age Care in Santa Monica Current System, Policy Options, and Recommendations - Pierson, Ashley (Research Reports, 2014)
In July 2012, the City of Santa Monica Human Services Division and the Santa Monica-Malibu Unified School District contracted with the RAND Corporation to conduct an assessment of child care programs in Santa Monica. The project sought to assess how well Santa Monica's early and school-age care programs meet the needs of families. Recommendations for improvement focused on advancing access, quality, service delivery, and financial sustainability.